Intensive Prenatal Nutrition Counseling in a Community Health Setting: A Randomized Controlled Trial. Issue 2 (August 2017) - Peccei, Alessandra; Blake-Lamb, Tiffany; Rahilly, Debra; Hatoum, Ida; Bryant, Allison
Abstract : OBJECTIVE: To assess the effect of a culturally appropriate nutritional intervention delivered to overweight and obese patients in a community health setting on gestational weight gain and postpartum weight retention. MATERIALS AND METHODS: We conducted a randomized controlled trial of an intensive nutrition counseling intervention for overweight and obese women by a registered dietitian throughout pregnancy and 6 months postpartum. The primary outcome was likelihood of gestational weight gain within Institute of Medicine (IOM, now known as the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine) guidelines. Secondary outcomes included birth weight and maternal and neonatal complications. RESULTS: Three hundred patients were randomized. In intent-to-treat analyses, assignment to the intervention group did not have a significant effect on maintenance of gestational weight gain within IOM guidelines (34.2% compared with 27.5%, odds ratio [OR] 1.4, 95% CI 0.8–2.4). Among obese women, assignment to the intervention group was associated with fewer large-for-gestational-age (LGA) neonates (7% compared with 17%; OR 0.3, 95% CI 0.1–0.99). Neither primary nor secondary outcomes were significantly different among overweight women in the intervention group in intent-to-treat analyses. In as-treated analyses, women in the intervention group had lower neonatal birth weights (3, 343 g compared with 3, 500 g; difference −157.4 g, 95% CI −298.4 to −16.5) and lower likelihood of LGA (6% compared with 14%; OR 0.4, 95% CI 0.2–0.96). Among overweight women, participation in the intervention was associated with lower gestational weight gain (26.1 pounds compared with 31.4 pounds; difference −5.3 pounds, 95% CI −10.0 to −0.6), lower neonatal birth weights (3, 237 g compared with 3, 467 g; difference −230, 95% CI −452.8 to −7.8), and lower percent of initial body mass index at 6 months postpartum (101% compared with 106%; difference −4.9, 95% CI −8.8 to −0.9). CONCLUSION: Our intervention did not result in a significant improvement in our primary outcome, the proportion of obese and overweight women who had gestational weight gain within IOM guidelines. However, intensive prenatal nutrition counseling offered in an urban community health setting may decrease LGA births among a group of overweight and obese women from culturally diverse backgrounds at risk for adverse maternal and neonatal outcomes. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01056406. Abstract : Intensive prenatal nutrition counseling offered in an urban community health setting may be associated with a decrease in large-for-gestational-age birth weights among obese women.